The influence of the Chinese sport system and Chinese cultural characteristics on Olympic sport psychology services - Si, G.; Duan, Y.; Li, H.-Y.; Zhang, C.-Q.; Su, N. (Psychology of Sport and Exercise, 2015)
Objectives: The purpose of this study was to investigate the influence of sociocultural factors on Chinese Olympic sport psychology services. Design and methods: Fifteen sport psychology consultants (SPCs), who served Chinese national teams for the 2008 Beijing Olympic Games, participated in this study after the Olympics. Semi-structured interviews were conducted within three months of the closing of the Olympics, followed by a hybrid approach to inductive and deductive thematic analyses. Results: Two general dimensions of sociocultural influence on Chinese Olympic sport psychology services were identified: (a) the Whole-Nation System and (b) Chinese cultural characteristics. They consisted of eight higher order themes, which comprised 26 lower order themes. This study revealed that Chinese sport psychology services were enhanced by recognizing the features of the Whole-Nation System (e.g., resource centralization and top-down management) and the successful blending of these features with Chinese cultural characteristics (e.g., holistic thinking style, keeping face and interpersonal order) into the psychological service. Conclusions: Sociocultural factors had a marked influence on Chinese Olympic sport psychology services, which enabled Chinese SPCs to provide a culturally competent service (e.g., prioritizing collective interests, respecting the authority of administrative officials and coaches, and keeping face with others) for the Beijing Olympic Games.